Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT PLN (Persero) UPT Malang - Safnidar, Hisyam Jodi; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the impact of work support and discipline on the work performance of PT employees. PLN (Persero) UPT Malang. This type of research is quantitative research where information is obtained through interviews with individuals who are respondents in the research. This research started from September 2023 to December 2023 with the population in this study is all employees of PT PLN (Persero) UPT Malang, a total of 191 people. The test used in this study is the Multiple Linear Regression Test. The result of this research is that work motivation and work discipline simultaneously affect the work performance of PT PLN (Persero) UPT Malang employees, part of work empowerment has an impact on the work of PT PLN (Persero) UPT Malang employees. Labor discipline affects the work of PT PLN (Persero) UPT Malang employees.” Keywords: Work Motivation, Work Discipline, Employee Performance.